How public media and governments co-construct the adult skills agenda. The OECD's Programme for the International Assessment of Adult Competencies in Italian and Danish newspapers. (11th September 2022) - Rasmussen, Palle; Milana, Marcella; Vatrella, Sandra; Larson, Anne
The 'Programme for the International Assessment of Adult Competencies' (PIAAC), developed and managed by the OECD, is an important source of knowledge about adult skills as well as an intervention in the field of education policy. One level of the intervention is the presence of PIAAC results in public media and debate. This article presents a comparative analysis of the way major newspapers in Italy and Denmark presented and used PIAAC over the period 2013–2019. The press contributes to constructing knowledge and setting agendas for education by presenting information structured from criteria of news value and from ideological stances. The analysis, done as part of the ENLIVEN research project (Milana et al., 2020 ), traces how PIAAC results were covered in Italian and Danish newspapers and used in the construction of themes, angles and 'truths' on skills and adult learning.